Pembaharuan Pemikiran Aqidah dalam Era Digital:Pendekatan Metodelogi Studi Islam - Nurfadila, Pani; Anantara, Fandey Lauda (Tihamah: Jurnal Studi Islam, 2024)
The development of digital technology has brought significant changes to various aspects of life, including the understanding and practice of faith (aqidah) among Muslims. This article examines the positive and negative impacts of digital transformation on the education of aqidah and ethics (akhlak), as well as the challenges and opportunities faced by the Muslim community in the digital era, such as radicalization, religious pluralism, and changes in social norms. Utilizing a library research method and a qualitative approach, this study explores how digital technology can be harnessed to enhance the understanding and application of aqidah values within society. The methodological approaches employed include historical, textual, anthropological, and philosophical perspectives to understand how aqidah can adapt and evolve amidst technological dynamics. The findings indicate that despite the complex challenges, the digital era also presents significant opportunities for the dissemination of Islamic teachings and the strengthening of aqidah in a broader and more effective manner. Therefore, it is essential to enhance innovative and responsive aqidah education in relation to technological advancements to ensure the continuity of Islamic values in the context of modern societal dynamics.